States as LBO specialists: evidence from Portugal - Alpalhão, R. (2016)
The paper’s purpose is to quantify the performance of a State in its action as a de facto LBO specialist, taking companies private to restructure them and subsequently reselling them in the share market. A sample comprising all the listed companies nationalized in Portugal in 1975 and 1976 that were subsequently privatised through a relisting by means of a share issue is constructed. The returns earned by the Portuguese Republic are computed, comparing the market values of nationalised companies at the time of their privatization with their theoretical value in a non-nationalization scenario. A negative abnormal return for the Portuguese Republic’s investment in shares is found. This negative return is much worse than the ones computed in similar work for France.